Structural Issues in the Kenyan Financial System: Improving Competition and Access - Beck, Thorsten; Fuchs, Michael (World Bank, Washington, D.C., 2013)
Although by regional standards, Kenya's financial system is relatively well developed and diversified, major structural impediments prevent it from reaching its full potential. Crosscountry comparisons, however, show the importance of a well-developed financial sector for long-term economic growth and poverty alleviation. Experience from other developing economies has shown the detrimental effect of government ownership and the positive impact that foreign bank ownership can have on the development of a market-based financial system. Analyzing and decomposing the high interest rate spreads and margins in Kenya helps identify structural impediments that drive the high cost of and low access to financial services. The limited information sharing on debtors, deficiencies in the legal and judicial system, the limited number of strong and reputable banks and non-transparency and uncertainty in the banking market are major impediments to the development of Kenya's financial system, to reducing spreads and to widening access.